The Attitudes of Indian Palliative-care Nurses and Physicians to Pain Control and Palliative Sedation - Gielen, Joris (Medknow Publications, 2011)
AIM: We wanted to assess Indian palliative-care nurses and physicians’ attitudes toward pain control and palliative sedation. MATERIALS AND METHODS: From May to September 2008, we interviewed 14 physicians and 13 nurses working in different palliative-care programs in New Delhi, using a semi-structured questionnaire, and following grounded-theory methodology (Glaser and Strauss). RESULTS: The interviewees did not consider administration of painkillers in large doses an ethical problem, provided the pain killers are properly titrated. Mild palliative sedation was considered acceptable. The interviewees disagreed whether palliative sedation can also be deep and continuous. Arguments mentioned against deep continuous palliative sedation were the conviction that it may cause unacceptable side effects, and impedes basic daily activities and social contacts. A few interviewees said that palliative sedation may hasten death. CONCLUSION: Due to fears and doubts regarding deep continuous palliative sedation, it may sometimes be too easily discarded as a treatment option for refractory symptoms.